Mental skills of National Hockey League players. - Barbour, Stuart A. (University of Ottawa (Canada), 1994)
The purpose of this study was to explore the mental skills used by professional ice hockey players and determine if Orlick's (1992) "Model of Human Excellence" could be applied to these athletes. In-depth interviews were conducted with 10 National Hockey League players who had collectively played over 4500 NHL games, and scored 1025 goals. The results indicated that Orlick's elements of commitment, belief, full focus, positive images, mental readiness, distraction control and, constructive evaluation were common to all subjects. The element of fun and enjoyment was also found to be significant for NHL players. The preservation of rich quotes and experiences offer valuable insights and strategies for aspiring hockey players. A survey of the mental aspects of professional hockey was also completed by 27 NHLers to corroborate the relative importance of each of the mental skills identified in Orlick's model. Overall the results were consistent with other research into the mental aspects of elite athletes.
Keywords: Psychology, Industrial.